Functional brain alterations in auditory hallucination subtypes in individuals with auditory hallucinations without the diagnosis of specific neurological diseases and mental disorders at the current stage - Xiaodong Lin; Chuanjun Zhuo; Gongying Li; Jie Li; Xiangyang Gao; Ce Chen; Deguo Jiang (Brain and Behavior, 2020)
Abstract Background We explored common and distinct pathological features of different subtypes of auditory hallucinations (AHs) to elucidate the underlying pathological mechanisms. Methods We recruited 39 individuals with constant commanding and commenting auditory verbal hallucinations (CCCAVHs), 49 with own thought auditory verbal hallucinations (OTAVHs), 46 with nonverbal AHs (NVAHs), 32 with replay AVHs (RAVHs), and 50 healthy controls. Functional connectivity density mapping was used to investigate global functional connectivity density (gFCD) alterations in these AH groups relative to the control group. Results We observed common brain functional alterations among four subtypes of AHs, such as increased gFCD in the bilateral superior temporal gyrus and mesial frontal lobe, and decreased gFCD in the bilateral medial prefrontal cortex. Increased gFCD was detected in the bilateral insula in CCCAVH individuals, bilateral thalamus in OTAVH individuals, bilateral precuneus in NVAH individuals, and bilateral hippocampus in RAVH individuals. The common and distinct gFCD alterations among four AH subtypes were located in main components of the frontoparietal, default mode, salience, central executive, and memory networks. Different AH subtypes exhibited specific aberrant patterns. Conclusions Our findings suggest that aberrant functional activity and metabolism in the abovementioned networks play key roles in the occurrence of AHs. Our findings provide evidence for distinct gFCD alterations in specific AH subtypes.